IDENTIFICATION OF ROCK CHARACTERISTICS USING XRF, XRD, AND SEM TESTS ON API ALAM IN PAMEKASAN - Joni, Idon; Vikki Ariyanto, Sandy (Indonesian Physical Review, 2022)
Research has been conducted into the nature of geothermal rocks in Pamekasan. This place is located in Tlanakan Pamekasan. This study aims to determine the composition of mineral compounds in the soil so that fire can burst out from the soil and the soil does not melt. Three steps can be done with simple refinement and filtering methods, namely X-Ray Fluorescence (XRF), X-ray diffraction (XRD), and Scanning Electron Microscope (SEM). The results of XRF analysis show the element of Api Alam 1 is Ca 66.2%, Api Alam 2 is Si 37.4%, and in hot springs, is Si 39.6%. The XRD results show that mineral qualitatively in Api Alam 1 was in the form of CaCO3 compound at 60.1% and SiO2 at 39.9%, while in Api Alam 2, hot water sources were in the form of SiO2 compound (>90%). SEM Results on Api Alam 1 show that the sample is almost homogeneous (the distribution of CaCO3 and SiO2 is uneven), the presence of slab-shaped clumps that identify the presence of varying grain size, and with high porosity, which indicates that the sample is partially amorphous in structure, in Api Alam 2. The Hot springs show irregular aggregations and poor homogeneity of the sample. The size of the three samples is ten Î¼m or 10.000 nm, while PSA results showed an average size of Api Alam 1 was 509.7 nm, Api Alam 2 was 891.3 nm, and Hot Springs was 468.3 nm.